Analysis of Risk on Common Stock of Commercial Bank in Nepal - Thapa, Narad Kumar (International Research Journal of MMC, 2022)
The study was conducted to analyze the risk on common stock of commercial bank in Nepal and to understand the risks and movements of the stock in relation to the market. The main objective of any investor in the market is to maximize the profit and reduce the risk. The paper helps the investor to know the snapshot of various statistical tools to be used to analysis the risk and return of the stocks. The study is based on conceptual research so the various research papers written from 2002 to 2021 have been reviewed. It is found that the various tools are used to measure the risk like standard deviation, beta, and coefficient of variation. The investor always needs to find a combination of higher return with low risk. The beta is useful to judge Systematic Risk. Thus, this study helps the investor to arrive at a conclusion and also to provide information about the performance of various banking securities in the market in terms of return and risk.